Development of blast, bacterial leaf blight resistant and drought tolerant rice variety through marker-assisted pedigree selection - Akos, Ibrahim Silas (2020)
Rice (Oryza sativa L.) is a staple food crop of over half of the world’s population. It provides over 21% of the food needs and about 76% calorie intake of Southeast population. Blast, bacterial leaf blight (BLB) and drought are the major stresses affecting rice cultivation globally including Malaysia. The objectives of this study were to identify the polymorphic markers linked to blast, BLB and drought resistance genes, to develop rice breeding lines by introgression of BLB and drought resistance genes into high yielding blast resistant variety (Putra-1), genotyping and selection of rice breeding lines that carry the blast and BLB resistance genes and drought QTLs, and to evaluate the performance of the improved rice breeding lines. In this study high yielding and blast disease resistant variety, Putra-1 was introgressed with IRBB60, a BLB resistant variety, and MR219-PL-137 drought tolerant QTLs line through marker-assisted pedigree selection. The selected polymorphic and linked markers for blast resistance were RM6836 (Piz, Pi2, Pi9 genes) and RM8225 (Piz gene), BLB resistance included, RM164, RM224 (Xa-4 gene), RM122, RM13 (xa-5 gene), RG136, Xa13Prom (xa-13 gene), RM21, pTA248 (Xa-21 gene). While tolerance comprised of QTL markers namely, RM1261, RM511; (qDTY12.1), RM520, (qDTY3.1) and RM236 (qDTY2.2.). Phenotyping was carried out to determine the levels of resistance at F4 generation for single cross, F3 for three-way cross and F3 for crossed lines. The scoring for blast, BLB disease pathogens inoculation and water deficit screening at reproductive-stage drought stress (RS) were resistant, moderately resistant and tolerant respectively. Agro-morphological and yield traits for non-drought stress (NS) showed that the progenies were similar in performance to their parental varieties but had significant differences among some of the improved lines on traits of days to 50% flowering (DTF), plant height (PH), panicle length number of tillers (TT), 100-grain weight (100-GW), fully filled grain (FFG), grain length and width ratio (GLW). At the RS, there were highly significant differences between the improved lines and susceptible variety for the traits of days to 50% flowering, panicle length, fully filled grains and yield maturity. There was interactions between reproductive-stage drought stress (RS) treatment and genotypes on panicle length, total number of tillers, fully filled grains, 100-grain-weight and grain length and width ratio, indicating that these traits were sensitive to the drought condition. Eleven selected improved lines namely lines PD14, PD15, PB12, PB15 derived from single cross carrying blast and drought genes (line code with PD), and blast with BLB genes (line code with PB), lines PBD1, PBD3, DPB7, DPB12, DPB13, DPB20 derived from three-way cross, (line code PBD and DPB) and PDB3 from double cross carrying blast, BLB and drought genes (line code PDB). Variation pattern determined by principal component analysis (PCA) showed that PBD1, PD15, PDB3, DPB13, DPB20 improved lines were found better for high FFG under (NS) condition. Three improved lines (PD15, DPB12, PBD3) comparatively had shown better performance under reproductive-stage drought stress condition. All the selected improved lines are recommended for large scale evaluation and utilisation in the future breeding programme for rice variety development of blast and BLB resistance, and drought tolerance characteristics.